The Relevance of John Dewey's Philosophy of Education in Early Childhood Development in the Digital Age - Sulistiawati, Sulistiawati (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study examines the relevance and application of John Dewey's educational philosophy in the context of early childhood education in the digital era. Dewey emphasized the importance of experiential learning (learning by doing) and social engagement as integral parts of an effective educational process. In facing the challenges and opportunities presented by technology, this study aims to explore how Dewey's principles can be applied to support the development of young children, particularly in using technology as a learning tool. The research uses a literature review method by analyzing various relevant sources on Dewey’s philosophy, early childhood education, and the integration of technology in education. The results indicate that technology can enrich children's learning experiences if used wisely, ensuring a balance between digital learning and direct exploration involving social interaction and physical activities. The role of teachers and parents in creating a balanced learning environment is crucial, where technology is used to support both individual and collaborative learning. The study also suggests that early childhood education curricula need to be adapted to be more responsive to technological developments and children's needs, integrating Dewey’s principles of direct experience and social involvement. Overall, this research contributes to the development of a more holistic and relevant educational curriculum in response to the challenges of the times, providing guidance for educators and parents in effectively using technology to support early childhood learning.